Anandamide suppresses pain initiation through a peripheral endocannabinoid mechanism - Clapper, Jason R. (2010)
Peripheral cannabinoid receptors exert a powerful inhibitory control over pain initiation, but the endocannabinoid signal that normally engages this intrinsic analgesic mechanism is unknown. To address this question, we developed a peripherally restricted inhibitor of fatty acid amide hydrolase (FAAH), the enzyme responsible for the degradation of the endocannabinoid anandamide. The compound, called URB937, suppresses FAAH activity and increases anandamide levels outside the central nervous system (CNS). Despite its inability to access brain and spinal cord, URB937 attenuates behavioral responses indicative of persistent pain in rodent models of peripheral nerve injury and inflammation, and prevents noxious stimulus-evoked neuronal activation in spinal cord regions implicated in nociceptive processing. CB(1) cannabinoid receptor blockade prevents these effects. The results suggest that anandamide-mediated signaling at peripheral CB(1) receptors controls the access of pain-related inputs to the CNS. Brain-impenetrant FAAH inhibitors, which strengthen this gating mechanism, might offer a new approach to pain therapy.